Morphological and Molecular Characteristics of Pufferfish Using DNA Barcode COI Gene at Camplong Beach, Madura, Indonesia - Adam Dwi Rangga; Viona Angelina Erlan Panjaitan; Endik Deni Nugroho; Dwi Anggorowati Rahayu; Cahya Ajeng Valentina Sulung; Rusdianto Rusdianto; Noorhidayah Binti Mamat (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research 1. Combining DNA barcoding with morphological variation analysis can enhance the accuracy of Pufferfish species identification. 2. This is the first study to examine the genetic diversity and phylogenetic relationships pufferfish from Madura, East Java, using partial COI sequences. 3. DNA barcoding confirms the morphological identification of this group (96%-100%) 4. The reliability using targeted DNA barcoding and phenetic taxonomy to study genetic variation and identify species differences in pufferfish. Abstract Pufferfish are one of the most common fish species in the ocean particularly in Camplong Beach, Madura. Despite their abundance, taxonomic information on pufferfish from East Java remains limited. Therefore, this study sought to identify pufferfish species in Sampang Regency through morphological and molecular characterization utilizing DNA barcoding of the COI gene. Fins were kept in 96% absolute ethanol, and DNA extraction, polymerase chain reaction (PCR), and sequence analysis were performed using bioinformatics tools, including the BOLD system and the web-based Automatic Barcode Gap Discovery (ABGD) tool. To strengthen genetic study, phenetic taxonomy was again applied using Ntysc. Morphological identification revealed five distinct species of pufferfish, namely Chelonodontops patoca, Lagocephalus spadiceus, Arothron reticularis, Ostracion rhinorhynchos, and Cyclichthys orbicularis. The high haplotype diversity (Hd) of 0.9 and nucleotide diversity (π) of 0.16270 indicated substantial genetic variation. There were 112 polymorphic sites, and the overall ts/tv ratio was 2.2. The frequency of parsimonious informative sites was 21.6%. The phylogenetic tree displayed distinct branching patterns among species. Morphological and molecular identification data supported these results, demonstrating that five distinct pufferfish species occur at Camplong Beach in the Sampang District of Madura.